Tradisi, Akal, dan Aksi: Studi Pendidikan Islam di Pondok Modern Ar Risalah - Ikhwan, Afiful (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2024)
This study explains the philosophical schools that form the Islamic education system at the Ar Risalah Modern Islamic Boarding School. As part of a modern Islamic educational institution in Indonesia. The purpose of this study is to describe and explain the impact of the three dominant Islamic philosophical schools, namely Religious-Conservative, Religious-Rational, and Pragmatic on the structure, curriculum, and learning activities at the Islamic boarding school. The approach used is a qualitative method with observation, interview, and document analysis techniques. The results of the study show that the Ar Risalah Modern Islamic Boarding School combines three approaches in its education. The conservative approach is seen in strengthening faith and worship in accordance with traditional Islamic teachings. The rational approach is seen in the way they encourage students to think openly and critically, and combine religious knowledge with general knowledge. Meanwhile, the pragmatic approach is seen in educational policies and curricula that are adjusted to the needs of the times. These three approaches form a balanced education system, which will maintain Islamic values, but is also able to adapt to the challenges of modern life.